Gestational Diabetes And Breast Feeding – Prospective Analysis For Post-Partum Glucose Intolerance (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Gestational Diabetes (GD) among women is increasing globally owing to the change in maternal dynamics such as age, elevated Body mass Index (BMI) and lifestyle changes. GD affected women are at a greater risk for post-partum diabetes. Breastfeeding practices may reduce this occurrence. The present study was conducted to assess the post partum glucose intolerance among gestational diabetes women who breast fed. Methodology: A prospective study was conducted on a cohort of 156 GD women and 304 control population between April 2021 to June 2022. Information on age, BMI and breastfeeding practices were obtained through a questionnaire. Oral Glucose Tolerance Test (OGTT) established confirmatory diagnosis for GD. Chi square and t test was applied to find differences between the groups, at lesser than 0.05 level of significance.Results: Breast feeding was practiced by 97.7% of the controls as compared to 83.9% of the GD group, which was considerably lower. GD women breast fed for 8.2000 + .8366 months as compared to controls for 10.7000 +.6708 months, which was significant at p =0.001. Glucose levels considerably reduced with prolonged breast feeding; the scores progressively reduced from 2 weeks to 12 months of post partum assessment. Conclusion: Breast feeding may play a significant role in reduction of post partum glucose intolerance in gestational diabetes women. Women must be motivated and supported to breast feed for the positive health outcomes of both the mother and the infant